THE ROLE OF THERAPEUTIC EXERCISE IN KNEE JOINT CREPITUS DURING SQUATTING: A NARRATIVE REVIEW OF BIOMECHANICAL AND BEHAVIORAL FACTORS - Kacper Melka; Patryk Matuszczak; Agata Pszczółka; Joanna Kozak; Gabriela Bajor; Mikołaj Szulewski; Aleksandra Salagierska; Patrycja Machno; Wiktoria Jurczyk-Florkiewicz; Zofia Gniadek (International Journal of Innovative Technologies in Social Science, 2026)
Background: Knee joint crepitus frequently occurs during functional activities such as squatting and is commonly reported by individuals with patellofemoral pain syndrome (PFPS). Although often considered a benign phenomenon, knee crepitus may influence movement-related beliefs, confidence, and activity participation. Therapeutic exercise represents a cornerstone of conservative PFPS management; however, its potential role in modifying knee joint crepitus and related movement behaviors remains insufficiently synthesized. Aim: To narratively review and synthesize current evidence regarding the potential effects of therapeutic exercise on knee joint crepitus during squatting, with particular consideration of biomechanical, neuromuscular, and psychosocial factors. Methods: A structured literature search was conducted in PubMed and Google Scholar for studies published up to February 2025. Randomized controlled trials, cohort studies, systematic reviews, and biomechanical analyses evaluating exercise-based interventions in PFPS populations were included. Given heterogeneity in study design and outcome measures, a narrative review methodology was adopted. Results: Exercise-based interventions consistently improved pain, function, and lower limb biomechanics in individuals with PFPS, a population in which knee crepitus is commonly reported. Hip and quadriceps strengthening combined with neuromuscular training improved movement control, reduced dynamic knee valgus, and optimized patellofemoral joint loading during squatting. Although knee crepitus was rarely assessed directly, these adaptations may influence mechanical and perceptual contributors to joint sound generation and movement confidence. Conclusions: Therapeutic exercise improves clinically meaningful outcomes in individuals reporting knee crepitus during squatting. While crepitus alone is not a reliable indicator of structural pathology, addressing it through exercise and patient education may reduce fear-avoidance behaviors and enhance functional participation. Further studies employing objective measures of knee joint crepitus are required to clarify direct intervention effects.